Role of Capsule in the Pathogenesis of Fowl Cholera Caused by Pasteurella multocida Serogroup A - Chung, Jing Yeng (American Society for Microbiology, 2001)
We have constructed a defined acapsular mutant in Pasteurella multocida X-73 (serogroup A:1) by disrupting the hexA gene through the insertion of a tetracycline resistance cassette. The genotype of the hexA::tet(M) strain was confirmed by PCR and Southern hybridization, and the acapsular phenotype of this strain was confirmed by electron microscopy. The hexA::tet(M) strain was attenuated in both mice and chickens. Complementation of the mutant with an intact hexAB fragment restored lethality in mice but not in chickens. In contrast to the results described previously for P. multocida serogroup B (J. D. Boyce and B. Adler, Infect. Immun. 68:3463–3468, 2000), the hexA::tet(M) strain was sensitive to the bactericidal action of chicken serum, whereas the wild-type and complemented strains were both resistant. Following inoculation into chicken muscle, the bacterial count of the hexA::tet(M) strain decreased significantly, while the wild-type and complemented strains both grew rapidly over 4 h. The capsule is thus an essential virulence determinant in the pathogenesis of fowl cholera.